As dificuldades de construção de projetos capazes de combater as desigualdades e a exclusão no Brasil: as reflexões de Fernando de Azevedo, Sérgio Buarque de Holanda, Celso Furtado e Raymundo Faoro - de Rezende, María José (Nómadas. Critical Journal of Social and Juridical Sciences, 2011)
The purpose of this article is to show that some Brazilian social thinkers (Fernando de Azevedo, Sérgio Buarque de Holanda, Celso Furtado and Raymundo Faoro) were committed to designing analyses proactively concerned with the transformation of the society as well as the Brazilian State. It is considered that, as men of science and men of action, they were searching for ways through which the country could build a civilizational project that should be understood as a nation‟s project, able to fight exclusions and inequalities in the several spheres of social life. Their reflections and action proposals for the building of a public and universal education, for the establishment of institutions and democratic political procedures and for the creation of effective mechanisms to income and resources, can be understood as part of their commitment towards substantial social changes in Brazil.